FOREST SEEDLINGS PRODUCTION USING STABILIZED SEWAGE SLUDGE - PAULA JR, DURVAL R. DE; PADOVANI, VERA C. R.; RICCI, ALEXANDRO B. (Revista Brasileira de Engenharia de Biossistemas, 2009)
Aiming tThis study aims at evaluating the physical, chemical and biological characteristics of sewage sludge and its feasibility for use as a component of substrata to produce seedlings of native and exotic trees. The sewage sludge was previously stabilized through the process of composting with grass remnants. Before and after the composting, chemical analyses were carried out in order to quantify levels of heavy metals, macro nutrients and micro nutrients in addition to microbiological analyses of sewage sludge. The mixtures (Treatments) in the proportions vary from 0 to 100% of organic compost of sewage sludge (OCSS) in composition with carbonized rice husks (CRH) and were compared to control treatments, which consisted of commercial substrates (PLANTMAX-EUCATEX) and cattle manure. Porosity, density, capacity of water retention and particles size of treatments were evaluated. Results of the physical characterization of substrates revealed that proportions ranging from 100 to 40% of the compost showed better results for tree seedlings cultivation. The use of organic compost of sewage sludge (OCSS) to produce seedlings of forest essences is a viable alternative for waste reuse, aggregating not only economy and quality of inputs in the yields, but also environmental benefits.